2016
DOI: 10.7554/elife.19267
|View full text |Cite
|
Sign up to set email alerts
|

Profound regulation of Na/K pump activity by transient elevations of cytoplasmic calcium in murine cardiac myocytes

Abstract: Small changes of Na/K pump activity regulate internal Ca release in cardiac myocytes via Na/Ca exchange. We now show conversely that transient elevations of cytoplasmic Ca strongly regulate cardiac Na/K pumps. When cytoplasmic Na is submaximal, Na/K pump currents decay rapidly during extracellular K application and multiple results suggest that an inactivation mechanism is involved. Brief activation of Ca influx by reverse Na/Ca exchange enhances pump currents and attenuates current decay, while repeated Ca el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(76 citation statements)
references
References 77 publications
6
69
1
Order By: Relevance
“…5, A and B, we studied Na/K pump function in mouse myocytes using half-maximal cytoplasmic Na concentrations and attempted to identify factors that might regulate pump activity. Surprisingly, from many classical signaling mechanisms examined, we found that in mouse myocytes, cytoplasmic Ca elevation caused the largest regulatory increases of Na/K pump activity (Lu et al, 2016). Fig.…”
Section: Secondary Regulation Of Na/k Pumps By Na-dependent Activationmentioning
confidence: 97%
See 3 more Smart Citations
“…5, A and B, we studied Na/K pump function in mouse myocytes using half-maximal cytoplasmic Na concentrations and attempted to identify factors that might regulate pump activity. Surprisingly, from many classical signaling mechanisms examined, we found that in mouse myocytes, cytoplasmic Ca elevation caused the largest regulatory increases of Na/K pump activity (Lu et al, 2016). Fig.…”
Section: Secondary Regulation Of Na/k Pumps By Na-dependent Activationmentioning
confidence: 97%
“…Accordingly, we suggested that pumps tend to inactivate (state 5 to state 6 transition) when they are oriented to the cytoplasmic side (i.e., in E 1 configuration) and their binding sites are not fully occupied by Na. We cannot exclude a possibility that cytoplasmic K binding may contribute to inactivation by forcing pumps backward in the cycle into stable K-occluded states, but cytoplasmic K is with good certainly not required for inactivation (Lu et al, 2016).…”
Section: Secondary Regulation Of Na/k Pumps By Na-dependent Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in cells transfected with Ser23 to Ala23 α1-mutants, the (Na + , K + )-ATPase cannot be phosphorylated by PKC (Poulsen et al, 2010). Phosphorylation of rat (Na + , K + )-ATPase α-subunit by an endogenous Ca 2+ /calmodulin-dependent protein kinase (CaMK) inhibits catalytic activity significantly (Netticadan et al, 1997) and constitutes part of a mechanism mediating Ca 2+ effects on the enzyme (Yingst et al, 1992; Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%